Sustainability Meets Strategy: Reaching the Environmentally Aware Consumer in the Fashion Industry - Lee, Yong Yu; Xia, Kun Peng; Lean, Peck Kwan; Kong, Yenny; Kwa, Jing Wen; Lai, Pei Shuang; Lai, Yik Theng; A., Stumaker; Ali, Anees Janee; Kee, Daisy Mui Hung (Advances in Global Economics and Business Journal, 2025)
This study investigates how perceived green product attributes and corporate environmental responsibility influence eco-conscious consumer attitudes, purchase intentions, and customer loyalty, using Uniqlo Malaysia as the research context. Drawing upon social identity theory and the Theory of Planned Behavior, we develop and empirically test a model linking environmental cues to loyalty outcomes. Data from an online survey (N=121) reveal that while both green product attributes and corporate environmental responsibility positively affect eco-conscious consumer attitudes, the latter exerts a stronger influence. Moreover, eco-conscious consumer attitude predicts purchase intention, which in turn drives customer loyalty. These findings highlight the mediating roles of attitude and intention in translating environmental perceptions into enduring loyalty. This study contributes to the green marketing literature by elucidating the mechanisms through which sustainability commitments foster trust and engagement. It also provides managerial insights, suggesting that genuine corporate-level environmental actions and transparent communication enhance brand credibility and long-term loyalty.